The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1525/can.2007.22.1.94
|View full text |Cite
|
Sign up to set email alerts
|

BIOETHNIC CONSCRIPTION: Genes, Race, and Mexicana/o Ethnicity in Diabetes Research

Abstract: Diseases that involve complex gene-gene-environment interactions (e.g., asthma, diabetes, heart disease) are the next frontier for genetic medicine. The Mendelian gold rush of the previous single-gene model has given way to a vastly more complex scientific venture. 1 Researchers must now transform "the environment" and at risk "populations" into variables that fit biological analyses while keeping in mind the speculative futures of potential drug markets, public health concerns and careerist imperatives. Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(114 citation statements)
references
References 64 publications
0
108
0
6
Order By: Relevance
“…Hogle, 1999;ScheperHughes, 2001), and social analyses tracking the rise of markets in racialized genomics (e.g. Fullwiley, 2007;Montoya, 2007;TallBear, 2008). Also absent are works theorizing recent transformations in capitalism and governance more generally (e.g.…”
mentioning
confidence: 99%
“…Hogle, 1999;ScheperHughes, 2001), and social analyses tracking the rise of markets in racialized genomics (e.g. Fullwiley, 2007;Montoya, 2007;TallBear, 2008). Also absent are works theorizing recent transformations in capitalism and governance more generally (e.g.…”
mentioning
confidence: 99%
“…Specifically, we do not simply assume that ethnicity 'means' different things to different researchers in different context; rather we seek to elucidate the research practices and dynamics through which ethnicity is 'made to be' in different ways in health research. The framework involved in this analysis is informed by two specific lines of research within the field of STS -attending to scientific practices and to the situatedness of these practices (Mol, 2002;Montoya, 2007;M'charek, 2013;Shim et al, 2014).…”
Section: Researching Ethnicity In the Context Of Healthmentioning
confidence: 99%
“…A second line of research has emerged from STS analyses of ethnicity and race in biomedical, health, and genomics research -namely situationality (Shim et al, 2014;Montoya, 2007;Epstein, 2010;Helberg-Proctor et al, 2016). Scientific practices involved in research on race and ethnicity in health and genomics have been shown to be situated in and shaped by various specific national, sociopolitical, and historical contexts (Hinterberger, 2012;Epstein, 2010;Tsai, 2010;Olarte Sierra and Díaz Del Castillo Herná ndez, 2014).…”
Section: Researching Ethnicity In the Context Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Evans (2010) critiques the 'anticipation of fatness' inherent in risk assessment as a form of 'pre-emptive politics' that supports rather than challenges a notion of fat as pathological. The hypothesis has been criticised for assuming that social structures and one's place within them remain static through the life course and generations (Vagero and Illsley, 1995) and for 'racialising' disease in using race as an operative concept (Montoya, 2007;Paradies et al, 2007;Poudrier, 2007). Important critiques address the ways in which the hypothesis is mobilised towards the biomedical control of women's reproductive bodies.…”
Section: Fat Transdisciplinesmentioning
confidence: 99%